2011
DOI: 10.1503/cmaj.100613
|View full text |Cite
|
Sign up to set email alerts
|

Trousseau sign in hypocalcemia

Abstract: A 50-year-old woman presented with a two-day history of diarrhea, vomiting, progressive numbness around her mouth and generalized body cramps. One year before presentation, she had undergone a total thyroidectomy for a multinodular goiter. She also had a history of depression, hypertension and chronic renal impairment. She reported taking citalopram, rabeprazole for gastroesophageal reflux disease, calcium carbonate, levothyroxine and vitamin B 12 . Her vital signs were stable. Trousseau sign was evidenced a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Cuff inflation, in conjunction with hyperventilation-induced hypocalcemia, likely triggered a classic Trousseau sign. 19 Cuff inflation to greater than the mean arterial pressure can result in the hand adopting a posture of metacarpophalangeal joint flexion with the interphalangeal joints of the fingers and thumb extended so that the thumb is in an opposing posture, as observed in our patient ( Figure 2B). This phenomenon has been reported in 1 to 4% of healthy individuals but has not been reported to be associated with cases of snakebite envenomation.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Cuff inflation, in conjunction with hyperventilation-induced hypocalcemia, likely triggered a classic Trousseau sign. 19 Cuff inflation to greater than the mean arterial pressure can result in the hand adopting a posture of metacarpophalangeal joint flexion with the interphalangeal joints of the fingers and thumb extended so that the thumb is in an opposing posture, as observed in our patient ( Figure 2B). This phenomenon has been reported in 1 to 4% of healthy individuals but has not been reported to be associated with cases of snakebite envenomation.…”
Section: Discussionsupporting
confidence: 57%
“…This phenomenon has been reported in 1 to 4% of healthy individuals but has not been reported to be associated with cases of snakebite envenomation. 19 Although Crotalus oreganus concolor myotoxic venom components can induce muscle contractile activity, causing rapid tetany-like hind limb hyperextension in mice (a symptom somewhat similar to the extension of the ankles, feet, and toes observed in our patient), this symptom was likely a stress-induced response rather than venom induced 20,22 Our patient's other myoneurologic symptoms of paresthesia, respiratory distress, and total body weakness may have been related to the high myotoxin content and concolor toxin in the Crotalus oreganus concolor's venom ( Figure 3, Table 1). Studies in mice injected with Crotalus oreganus concolor venom showed they died from rapid respiratory failure, suggesting that venom may have contributed to our patient's respiratory difficulty, as has been reported to occur after C scutulatus, C cerastes, C oreganus helleri, and C horridus envenomation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some of these similar initial ensuing symptoms such as the patient's tetanic bursts, which could be described as carpopedal spasms, may not have been venom-induced, but rather have potentially resulted from patient anxiety-induced hyperventilation. These myoneurological symptoms could also have been triggered by sphygmomanometer cuff inflation (Mrunalini et al, 2014;Rehman and Wunder, 2011). Additionally, the symptoms of blurred vision, weakness, perioral paresthesia, and difficulty breathing have also been reported in other cases of North American rattlesnake envenomation, including C. o. concolor envenomation (Bush and Siedelburg, 1999;LoVecchio et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The monitoring of vital signs in venomous snakebite patients, specifically blood pressure measurements, often involves the use of a sphygmomanometer with an inflatable cuff. Our patient had his blood pressure monitored during ambulance transport, and the question of whether or not the inflation of the cuff, in conjunction with hyperventilation-induced hypocalcemia, triggered a classic Trousseau sign also has to be considered (Rehman and Wunder, 2011). Cuff inflation to greater than the mean arterial pressure can result in the hand adopting a characterized posture of flexion of the metacarpophalangeal joints, with the interphalangeal joints of the fingers and thumb extended so that the thumb is in an opposing posture, as observed in our patient (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Common symptoms of hypocalcaemia include fatigue, weakness, irritability, confusion and mood changes. Pathognomonic signs of hypocalcaemia are Trousseau's sign (carpopedal spasm occurs when a blood pressure cuff inflated above the systolic blood pressure) and Chvostek's sign (facial muscle spasm following tapping over the facial nerve) [25]. These signs occur due to neuromuscular excitability [26].…”
Section: Clinical Manifestations Of Hypocalcaemiamentioning
confidence: 99%